34.3k views
3 votes
Solve for n and p by using substation 6n +2p =-3 and 4n + 2p= -1

User Sheff
by
4.9k points

1 Answer

4 votes

Let's subtract the equations. To do this let's multiply by (-) the second equation and sum:


\begin{gathered} +6n+2p=-3 \\ -4n-2p=+1 \\ -------- \\ +2n+0p=-2 \end{gathered}

Now simplify


\begin{gathered} 2n=-2 \\ n=(-2)/(2) \\ n=-1 \end{gathered}

Now replacing the n value in the first equation


\begin{gathered} 6(1)+2p=-3 \\ 6+2p=-3 \end{gathered}

Solving for p


\begin{gathered} 2p=-3-6 \\ p=-(9)/(2) \end{gathered}

Answer: n=-1 and p=-9/2

User Goat
by
5.7k points